Takhrij Hadith Muslim's Obligation to Seek Knowledge - Permana, Muhammad Idham Hafizh; Fananie, Kifah Gibraltar Bey (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about studying. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith in tahe field of takhrij hadith, while the material object is the hadith about studying with narrated by Ibn Majah No. 224. The results and discussion of this study indicate that the hadith narrated by Ibn Majah no. 224 is dhaif because there are comments from scholars who give negative assessments of the hadith narrators but are promoted to hasan li ghairihi because they have syahid and muttabi. This study concludes that the hadith narrated by Ibn Majah no. 224 has the qualifications of maqbul ma'mul bih so that it is relevant to be used as a proposition in the obligation to study.